Risk factors for antibiotic resistance in Streptococcus pneumoniae - Klugman, Keith (Henry Stewart Talks, 2009)
Antibiotic use as a driver of resistance in Streptococcus pneumoniae at the country, provincial and individual level, Drivers of multiple resistance, Conjugate pneumococcal vaccine impact on antibiotic resistance in the pneumococcus
Reviewed at 2022/04/12